GAYA PSYCHEDELIA COUNTER CULTURE AMERIKA KOMODIFIKASI INDONESIA KINI - Banindro, Baskoro Suryo (Institute of Research and Community Outreach - Petra Christian University, 2007)
The art of psychedelia is an example of art that uses a nationâ€™s cultural consciousness as a source of expression of the past. Conceptually, the spirit of this art is to connect the modern movement with the effects of drug use. The American youths utilized this movement as counter culture that gave the birth to the flower generation in a settled community. Psychedelic style which in the beginning was an identity, a symbol of anti settledness, and Uncle Samâ€™s youthâ€™s fight against its politics in the 1960â€™s. At the end it became the signs of times. The zeitgeist movement in the next decade entered Indonesia with new packaging that transforms into comodification that can be applied to various media through popular culture of its youths. Abstract in Bahasa Indonesia: Seni penggunaan kesadaran budaya bangsa untuk diubah sebagai sumber pengungkapan yang terjadi di masa lalu salah satu contohnya ialah â€œseni psychedelicâ€. Secara konseptual jiwa seni ini ialah menghubungkan kepada pergerakan modern yang berhubungan dengan perasaan yang diakibatkan oleh pengaruh obat bius. Kaum muda Amerika memanÂ¬faatÂ¬kan pergerakan ini sebagai budaya tanding â€œcounter cultureâ€ yang melahirkan â€œgenerasi bungaâ€ di komunitas yang telah mapan. Gaya psychedelia yang pada mulanya dijadikan â€œjati diriâ€ dan simbol anti kemapanan dan perlawanan kawula muda negara â€œPaman Samâ€ terhadap kebijakan politik di negaranya tahun 1960an, pada akhirnya menjadi sebuah penanda jaman. Gelombang â€œzeitgeistâ€ ini pada dekade berikutnya masuk ke Nusantara dengan â€œkemasan baruâ€ yang menjelma dalam bentuk komodifikasi yang aplikatif di berbagai media melalui budaya popular yang lekat di hati generasi muda Indonesia. Kata kunci: gaya, psychedelic, counter culture, komodifikasi.